HUBUNGAN BEBAN KERJA MENTAL TERHADAP KEBAHAGIAAN DI TEMPAT KERJA PADA KARYAWAN PT MITRA INOVASI GEMILANG TAHUN 2022 - Andini Maulani Putri (2023)
Employee happiness at work greatly influences the success and performance of the organization in achieving the organization's main goals. Unhappy workers will affect low productivity, decreased performance, increased absenteeism and sick leave, fatigue, burnout, and the emergence of various health problems. The urgency of the mental workload has increased since the existence of computerized technology, which demands employees' cognitive abilities. An inappropriate mental workload will affect employee happiness at work. This study aimed to examine the relationship between mental workload and workplace happiness among PT Mitra Inovasi Gemilang employees in 2022. The study was cross-sectional and took place between October and December of 2022. The independent variables of this study consisted of mental workload and covariate variables (age, gender, and employment status). With inclusion and exclusion criteria, the study population was 72 people, so the sample size was 70 people. Data analysis was univariate and bivariate using the chi-square test. The results of the bivariate test showed that the mild category of mental workload (0.025) and the moderate category of mental workload (0.041) were related to employee workplace happiness. As for the covariate variables, namely age (0.394), gender (0.455), and employment status (0.005). Factors related to employee happiness in this study are mental workload and worker status. In addition, PT Mitra Inovasi Gemilang's employees' mental workload is in the moderate category. It is important to assess employee capabilities first before assigning workload, training and education related to stress management, and policies that support employee workplace happiness.